A szolgáltatások osztályozása és szerepük a regionális fejlődésben - Raffay, Zoltán (Tér és Társadalom, 1996)
On the classical view, the role of the service sector in the economy is not very important, they don't produce new value, but consume the products, made by the other sectors, like parasite. In the 30s, some researcher began to attrack the attention, that as they society got richer, the people spend more money to services. The new working places were created most in the service sector, instead of the manufacturing. The research of the service sector concentrated mostly on final consumption, to study the services offered for the households. On the second part of the 80s the attention turned to the productive services, these are so companion services, which are consumed in the commodity production and consumer services, too. The observations of the most developed countries show, that beside the manufacturing - the classical engine of the economic development - to interweaved with it, the business services play more and more important role in the regional development, in that regions, which show outstanding achievment of developing accelerance. The personal or household, and the clearly common services become a very important device to attract and to protect the human resources - the most important production factor.